Analysis of the Revocation of the Lawsuit for Unlawful Acts Before the Defendant's Answer to the Determination Study Number 203/Pdt. G/2022/Pn Plk at the Palangka Raya District Court - Azani, Anggira; Farina, Thea; Wijaya, Andika (Dinasti Research, 2025)
In the Indonesian civil law system, the plaintiff’s ability to withdraw a lawsuit before the defendant responds is a key procedural aspect regulated by Article 271 of the Reglement op de Burgerlijke Rechtsvordering (Rv). This analysis explores the application of this rule in Determination Number 203/PDT.G/2022/PN PLK at the Palangka Raya District Court, where the plaintiff, Porwanto, withdrew a lawsuit for unlawful acts against three defendants before their response. The court approved the withdrawal, ordered the plaintiff to pay court costs of Rp2,160,000, and removed the case from the register. This case reflects the balance between plaintiff autonomy and judicial efficiency, yet it raises concerns about potential procedural abuse. This study underscores the need for strict oversight to ensure such flexibility does not compromise fairness for all parties involved.